Minimálne invazivní torakoskopicky asistovaný transdiafragmatický prístup pri osetrování predního sloupce torakolumbálního prechodu - Kocis, J; Wendsche, P; Muzík, V; Bilik, A; Veselý, R; Cernohousová, I (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2009)
PURPOSE OF THE STUDY: A retrospective analysis of patients with thoracolumbar junction fractures who underwent video-assisted thoracoscopic surgery via a minimally invasive approach (minithoracotomy) for reconstruction of the anterior spinal column. MATERIAL: Between 2002 and 2006, a total of 127 patients were treated by this technique. The age of the group, including 75 men and 52 women, ranged from 18 to 75 years (average, 45.9 years). L1 and Th12 fractures were treated in 71 and 66 patients, respectively. Based on CT scans and operative findings, the fractures were assessed as type A in 81, type B in 42 and type C in four patients. The causes of injury were a fall from height in 72, a pedestrian's fall in 29, a traffic accident in 23 and other in three patients. On admission 19 patients had a neurological deficit of varying degree: Frankel grade A, eight patients; grade B, four; grade C, five; and grade D, two patients. METHODS: The patients were treated by either posterior stabilization and, at the second stage, the minimally invasive technique via an anterior approach, or the minimally invasive anterior procedure alone. Transpedicular posterior stabilization was performed in 52 patients. All of them had an anterior procedure completed with screw-rod-screw stabilization, and the vertebral body was replaced with an allograft or an expandable titanium cage in 50 and two patients, respectively. The anterior approach alone was used in 75 patients, who received a bisegmental angle-stable implant in 43 and a monosegmental plate in 32 cases. To replace the vertebral body, allografts were used in 71 and an expandable titanium cage in four patients. RESULTS: The average follow-up period was 3.9 years (range, 1 to 6 years). In the anterior procedure, the average operative time was 90 min (range, 50 to 130 min) and blood loss ranged from 200 ml to 2300 ml. A complication due to deep infection occurred in one patient and required removal of both the anterior and posterior implants. Bony fusion without complications was achieved in all patients within a year of surgery. The loss of correction after the anterior procedure with an allograft or titanium cage was up to 2 degrees at 1-year follow-up. No conversion of the minimally invasive technique to a conventional approach due to visceral or vascular injury was necessary; nor was revision surgery for fluidothorax needed. No loosening of an anterior implant or cage dislocation was recorded. Hypesthesia in the operative wound area was found in four patients (3.1%). Improvement in neurological status by at least one Frankel grade was found in 10 of the 19 affected patients. DISCUSSION: The anterior approach is recommended for reconstruction of the anterior spinal column in burst fractures of the thoracolumbar junction in particular. An isolated posterior approach may result in implant failure during bony union or in the loss of correction after implant removal that can lead to the recurrence of kyphosis. Conventional thoracotomy is often associated with significant morbidity and hence there is a need for a minimally invasive approach to treat thoracolumbar junction injury. CONCLUSIONS: The minimally invasive approach (minithoracotomy up to 6-7 cm) combined with thoracoscopy is an alternative to an exclusively endoscopic technique enabling us to provide safe surgical treatment of the anterior spinal column.
Keywords: Young Adult; fraktury páteře; Male; Fracture Fixation, Internal; Thoracic Vertebrae; mladý dospělý; vnitřní fixace fraktury; Adolescent; Adult; Aged; dospělí; mužské pohlaví; senioři; hrudní obratle; mladiství; lidé; ženské pohlaví; bederní obratle; Humans; Lumbar Vertebrae; Spinal Fractures; Thoracic Surgery, Video-Assisted; hrudní chirurgie video-asistovaná; Female; lidé středního věku; ortopedické výkony; Orthopedic Procedures; Middle Aged